Presumption of innocence in the civil sphere? An analysis of the proposals of Eduardo da Fonseca and J. Harvie Wilkinson III - Alarcón Donayre, Diego (2020)
This paper examines the presumption of innocence idea in the civil sphere developed by Eduardo da Fonseca and J. Harvie Wilkinson III. For this objective, it analyzes the assumptions of both proposals. They are elaborated on the basis of the relationship between the conception of punishment and the moral and political criteria associated with the determination of standards of proof. In this sense, it reveals two problematic aspects common to both conceptions consisting of: first, the implicit adoption of a nominalist perspective on punishment, and second, the absence of a discussion of the moral and political criteria that justify both the exclusivity of the presumption of criminal innocence and its expansion to the civil sphere. It is concluded that the answer to the question of the possibility of a presumption of civil innocence requires metaethical and political philosophy notions that both proposals fail to develop.